AN OVERVIEW OF COMPUTATIONAL POTENTIALS IN NIGERIA FOR DESIGNING A NUCLEAR REACTOR SYSTEM FOR RESEARCH OR POWER APPLICATION - Salawu, A.; Suleiman, S. A (FUDMA JOURNAL OF SCIENCES, 2023)
Nigeria, with seven nuclear research centers has no technical know-how to develop and operate a nuclear power plant for electrical production, 38 years after the introduction of nuclear program in the country. Our goal in this study is to provide a review of Nigeria's potentials to fabricate a nuclear reactor system for research or power application. Generally, Reactors are first designed and tested on paper before the actual manufacture and the real systems are expected to behave as predicted by reactor physics computer calculations. Countries usually designed new reactor system by studying the success records of other countries, by reviewing its own previous experience, or by the availability of nuclear materials. Nigeria must engage the services of the local scientists to design a reactor system for the development of the country's nuclear power program. Over-dependence on the imported finished products and services has retarded the growth of science and technology in Nigeria. The proposal to acquire four nuclear power plants from a foreign firm without tasking our local scientist to design and develop such facility for Nigeria might not speedup the growth of the country’s nuclear energy program. Nigeria can study the success records of sister countries to develop its own experience on the use of nuclear energy for electrical production. This will have a more positive impact on the growth of the Nigeria nuclear power program as compared to engaging the service of foreign experts to design, construct, operate and decommission a nuclear power plant for electrical production in
Keywords: Reactor, Design, Power, Plant, Computer, Codes, Electrical, Fission, Energy, Nigeria